Uma abordagem computacional para previsão de demanda de energia elétrica e apoio à tomada de decisão no mercado de curto prazo no Brasil - Bezerra, Francisco Elânio (2017)
The technological advance, in the world, has brought about profound changes in the way the electric energy is generated, distributed and consumed. The increase in electricity consumption and the interruption of power supply in Brazil led to the creation of Decree 5.163/2004, proposing a new model for the sale of electricity in the National Interconnected System through auctions in the free contracting environments between buyers and Sellers, or regulated through auctions promoted by the Electric Energy Trading Chamber (CCEE), which accounts for the difference between contracting and energy consumption and through the settlement price of the differences and promotes the settlement of this energy short-term market .If you have more contracts than consumption, or more consumption than contracts, you will suffer penalties. With the change in the commercialization of energy, the generators and distributors suffer with forecast of consumption and with amount of energy that must contract in the auctions. In this scenario, several techniques such as genetic algorithm, multicriteria decision, fuzzy logic, artificial neural networks among others have been used to optimize the system of buying and selling energy in this new environment. Therefore, the proposal of this work is to develop an intelligent computational system, using historical data from a distributor to forecast demand by consumption class to support decision making in the short term market. The result of the work may provide conditions for a distributor to monitor energy demand by consumption class, provide possibilities for short-term market trading and minimize losses with subcontracting and over-contracting.